2013
DOI: 10.1111/tra.12132
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Clathrin‐Mediated Trafficking Causes Centrosome Overduplication and Senescence

Abstract: The Hsc70 cochaperone, G cyclin-associated kinase (GAK), has been shown to be essential for the chaperoning of clathrin by Hsc70 in the cell. In this study, we used conditional GAK knockout mouse embryonic fibroblasts (MEFs) to determine the effect of completely inhibiting clathrin-dependent trafficking on the cell cycle. After GAK was knocked out, the cells developed the unusual phenotype of having multiple centrosomes, but at the same time failed to divide and ultimately became senescent. To explain this phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…In another model, it was demonstrated that knockout of GAK results in destabilization of the lysosomal membrane and leakage of iron, causing DNA damage. 28 Genetic markers around GPNMB were identified and replicated in several GWASs, with approximately 10% risk reduction. 7,9 Interestingly, GPNMB is an important gene in melanoma, 187 a skin malignancy that is associated with PD.…”
Section: Maptmentioning
confidence: 99%
“…In another model, it was demonstrated that knockout of GAK results in destabilization of the lysosomal membrane and leakage of iron, causing DNA damage. 28 Genetic markers around GPNMB were identified and replicated in several GWASs, with approximately 10% risk reduction. 7,9 Interestingly, GPNMB is an important gene in melanoma, 187 a skin malignancy that is associated with PD.…”
Section: Maptmentioning
confidence: 99%
“…5 Thus, GAK is essential for cell growth because GAK knockout (GAK ¡/¡ ) mice display embryonic lethality 6 and mouse embryonic fibroblasts (MEFs) derived from GAK ¡/¡ mice fail to divide and ultimately become senescent. 7 This phenotype is independent of the Ser/Thr kinase activity of GAK because the cell cycle of MEFs derived from knockout mice expressing a kinase-dead form of GAK is normal. 8 GAK is overexpressed in nuclei of various cancer cells and the GAK expression level is positively correlated with malignancy in surgical specimens from prostate cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…For adenoviral infection, cells plated 1 day before infection were incubated in fresh DMEM culture medium with adenovirus expressing Cre recombinase (Ad-Cre; Vector Biolabs) at a multiplicity of infection (MOI) of 200 in the presence of 5 µg/ml polybrene (Sigma-Aldrich), as described previously (Olszewski et al, 2014). The stable cell lines were treated with adenovirus as described above to knockout the endogenous GAK.…”
Section: Cell Culture and Ad-cre Infectionmentioning
confidence: 99%